PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP RISIKO KEBANGKRUTAN PADA PT. MATAHARI DEPARTMENT STORE TBK - Priatna Kesumah; Valerie Theophanye; Ersa Novell Ramadhanti; Shilmi Fadhilla Syam; Aghniya Sabila Novaghiya; Gunardi Gunardi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
The problem of financial difficulties is a major problem that every company must experience, this also happens to PT. Matahari Department Store Tbk. Research results show that in 2018-2020 from the results of the current ratio analysis showed a decrease by an average of 90%. Meanwhile, the results of the quick ratio showed an increase in 2019, but experienced a significant decrease in 2020 with an average of 50%. Based on the analysis of current ratio and fast ratio shows that the financial performance of PT Matahari Department Store Tbk in terms of current ratio is classified as "poor". The results of ROA analysis in 2019 increased, but in 2020 there was a significant decrease with an average ratio of 12%. In addition, according to the analysis results from ROE, the average recorded ratio is 38%.